Design, Characterization, and Anticancer and Antimicrobial Activities of Mucoadhesive Oral Patches Loaded with Usnea barbata (L.) F. H. Wigg Ethanol Extract F-UBE-HPMC - Violeta Popovici; Elena Matei; Georgeta Camelia Cozaru; Laura Bucur; Cerasela Elena Gîrd; Verginica Schröder; Emma Adriana Ozon; Mirela Adriana Mitu; Adina Magdalena Musuc; Simona Petrescu; Irina Atkinson; Adriana Rusu; et al. (MDPI AG, 2022)
The oral cavity's common pathologies are tooth decay, periodontal disease, and oral cancer; oral squamous cell carcinoma (OSCC) is the most frequent oral malignancy, with a high mortality rate. Our study aims to formulate, develop, characterize, and pharmacologically investigate the oral mucoadhesive patches (F-UBE-HPMC) loaded with Usnea barbata (L.) F.H. Wigg dry ethanol extract (UBE), using HPMC K100 as a film-forming polymer. Each patch contains 312 µg UBE, with a total phenolic content (TPC) of 178.849 µg and 33.924 µg usnic acid. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) were performed for their morphological characterization, followed by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and thermogravimetric analysis (TGA). Pharmacotechnical evaluation involved the measurement of the specific parameters for mucoadhesive oral patches as follows: weight uniformity, thickness, folding endurance, tensile strength, elongation, moisture content, pH, disintegration time, swelling rate, and ex vivo mucoadhesion time. Thus, each F-UBE-HPMC has 104 ± 4.31 mg, a pH = 7.05 ± 0.04, a disintegration time of 130 ± 4.14 s, a swelling ratio of 272 ± 6.31% after 6 h, and a mucoadhesion time of 102 ± 3.22 min. Then, F-UBE-HPMCs pharmacological effects were investigated using brine shrimp lethality assay (BSL assay) as a cytotoxicity prescreening test, followed by complex flow cytometry analyses on blood cell cultures and oral epithelial squamous cell carcinoma CLS-354 cell line. The results revealed significant anticancer effects by considerably increasing oxidative stress and blocking DNA synthesis in CLS-354 cancer cells. The antimicrobial potential against Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 27353, Candida albicans ATCC 10231, and Candida parapsilosis ATCC 22019 was assessed by a Resazurin-based 96-well plate microdilution method. The patches moderately inhibited both bacteria strains growing and displayed a significant antifungal effect, higher on C. albicans than on C. parapsilosis. All these properties lead to considering F-UBE-HPMC suitable for oral disease prevention and therapy.